RANCANGAN PEMASANGAN LAMPU PENERANGAN JALAN MENUJU MASJID RAUDATUL ILMI SEKOLAH TINGGI PENERBANGAN INDONESIA - Ewanda Rakadifa; Harman Sudjantyo; Suse Lamtiar S (Politeknik Penerbangan Indonesia Curug, 2017)
In this study the author discusses the design of street lighting from Prawyasa Kindergarten to Raudhatul Ilmi Mosque by recalculating manually using formulas and standards in accordance with SNI. After getting the calculation results manually, the calculation results are then simulated in a software Dialux Evo Version 6.1. The output of this dialux software can feature a powerful simulation of street lighting from the Prawyasa Kindergarten path to the Raudhatul Ilmi Mosque in the Indonesia Civil Aviation Institute.